Preparation and Characterization of Mangrove (Rizhopora Mucronata) Charcoal-Epoxy Polymer Composite - Althaf Irfan Fachrezy; Ryan Sutedja; Sartika Selang; Aster Rahayu; Maryudi - Maryudi (Universitas Ahmad Dahlan, 2022)
Composite materials have been widely developed and applied for various purposes. Polymer composites have excellent properties on mechanical strength and chemical resistance. This study aims to determine the strength of composite made of mangrove charcoal and epoxy since mangrove charcoal has a good character and is abundantly available. The mangrove charcoal was added into the epoxy-hardener matrix with a volume fraction of 10%, 20%, and 30%. The charcoal size was 40, 60, and 100 mesh. The highest tensile strength was found with a volume fraction of 10% with an average of 19.33 N/mm2 at a size variation of 100 mesh mangrove charcoal. The highest elongation at break was found with a volume fraction of 10% with an average of 5.233% at 100 mesh mangrove charcoal size.